Determining the levels of pelvic floor disorders in women diagnosed with urinary incontinence: a mix-method study - Yalazı, Rüveyda Ölmez; Demirci, Nurdan (Frontiers in Medicine, 2025)
IntroductionUrinary incontinence (UI) significantly affects women’s quality of life and may contribute to pelvic floor disorders. This study aimed to investigate the impact of UI on pelvic floor disorders through a mixed-methods approach.MethodsA convergent parallel design was employed, integrating quantitative and qualitative data. Quantitative data were collected using the “Global Pelvic Floor Disorders Questionnaire,” and semi-structured interviews were conducted for qualitative insights. Quantitative data were analyzed using SPSS 26.0, while qualitative data underwent content analysis with MAXQDA Pro 22 software.ResultsAmong the participants, 41.7% were diagnosed with stress urinary incontinence, which was associated with the highest level of discomfort. Qualitative findings revealed four main categories: effects on daily life, emotional and psychological effects, coping strategies, and treatment approaches and expectations. Participants reported that UI led to social isolation, reduced self-esteem, and increased anxiety.DiscussionThe findings highlight that UI adversely affects both the physical and psychosocial well-being of women. Addressing this condition requires a holistic approach combining medical treatment with psychosocial support to mitigate its multifaceted impact.